Development and sensory evaluation of edible flower incorporation in pastry products using avant-garde techniques - Mendoza Guevara, Kluivert Raúl; Paz Sánchez, Javier Alfonso; Bohórquez-Medina, Sofía Lorena; Bohórquez- Medina, Andrea L. (Hasanuddin University Food Science and Technology Study Program, 2025)
Edible flowers have traditionally been used as decorative elements in haute cuisine, their potential as a main ingredient in the creation of distinctive flavors has been little investigated, especially in the field of pastry. The aim of this research was to develop a gastronomic proposal that utilizes innovative techniques for incorporating edible flowers into pastry products and to evaluate their acceptability. The edible flowers used in this study were Hibiscus (Jamaica), Jasmine, and Lavender. For each flower, three samples were prepared with varying concentrations. To determine the optimal formulation and its acceptability, a sensory evaluation was conducted with an expert panel consisting of 10 participants. The panel assessed key attributes, including aroma, color, flavor, texture, aftertaste, and overall acceptability, using a 9-point Likert scale. The findings revealed that Hibiscus sample 1, with a dosage of 15 g, was the most acceptable, making it ideal for use in pastry creams. For Jasmine, sample 3, containing 5 g, was preferred, while for Lavender, sample 2, with 3 g, was favored due to the flower’s more intense flavor. This research proposes using edible flowers as the main element in pastry products, demonstrating their successful integration into various preparations and their role as unique components in desserts.